CORPOREITY IN PHYSICAL EDUCATION?! (Fiep Bulletin - online, 2012)
Discuss the corporeity in Physical Education is an instigating and opportune topic. The considerations highlighted tovisualize the understanding of corporeity and its manifestations in Physical Education classes, especially at school. The objectiveof this study was to reflect the corporeity, with the dressage body and fragmentation of the body its categories of analysis. To thisend, we used a qualitative and basic research for understanding the subject.
Keywords: Corporeity; Physical Education; Dressage Body.